2013
DOI: 10.1371/journal.pone.0082486
|View full text |Cite
|
Sign up to set email alerts
|

Phylodynamics of the Emergence of Influenza Viruses after Cross-Species Transmission

Abstract: Human populations are constantly exposed to emerging pathogens such as influenza A viruses that result from cross-species transmissions. Generally these sporadic events are evolutionary dead-ends, but occasionally, viruses establish themselves in a new host that offers a novel genomic context to which the virus must adjust to avoid attenuation. However, the dynamics of this process are unknown. Here we present a novel method to characterize the time it takes to G+C composition at third codon positions (GC3 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…This raises the question of whether using longer gene segments or whole genomes provides deeper resolution into the evolutionary history of rapidly evolving pathogens. Past influenza A studies (41,123,124), including the present study, showed that HA and NA segments typically exhibit higher evolutionary rates than more conserved segments like PB1 and PB2. Subsequently, segments with higher evolutionary rate will also display stronger evolutionary signals, as described above.…”
Section: Robustness and Limitations Of Phylodynamic Methodssupporting
confidence: 49%
“…This raises the question of whether using longer gene segments or whole genomes provides deeper resolution into the evolutionary history of rapidly evolving pathogens. Past influenza A studies (41,123,124), including the present study, showed that HA and NA segments typically exhibit higher evolutionary rates than more conserved segments like PB1 and PB2. Subsequently, segments with higher evolutionary rate will also display stronger evolutionary signals, as described above.…”
Section: Robustness and Limitations Of Phylodynamic Methodssupporting
confidence: 49%
“…In addition, the U content of each gene segment was analysed for both H3N8 CIV and H3N8 EIV. An increasing U content in viral gene segments is an indicator of viral adaptation to a new host species [64]. There was an increasing trend in the U content of each gene segment over time for both H3N8 CIV and H3N8 EIV (Figure 8), indicating that both viruses were adapting to their respective hosts.…”
Section: Discussionmentioning
confidence: 99%
“…In both vaccinated and non-vaccinated pigs, influenza A viruses can be diverse at the level of the population, within an individual pig, and even within a cell [72][73][74][75]. Investigation of virus characterization and of transmissibility is necessary to understand, at the individual animal level, vaccine induced cross-protection and duration of immunity, and at the population level, the impact of vaccination on the viral ecology of influenza in swine [1,21,56,[76][77][78][79][80][81][82]. In poultry, vaccination has been associated with selective transmission of more virulent strains of IAV [83].…”
Section: Plos Onementioning
confidence: 99%